Long-Term Outcome Up To 40 Years after Single Patch Repair of Complete Atrioventricular Septal Defect in Infancy or Childhood - Reynen, Stefanie; Hövels-Gürich, Hedwig H.; Vazquez-Jimenez, Jaime F.; Messmer, Bruno J.; Sachweh, Joerg S. (The Thoracic and Cardiovascular Surgeon, 2021)
Objectives Patients with repaired complete atrioventricular septal defect (CAVSD) represent an increasing portion of grown-ups with congenital heart disease. For repair of CAVSD, the single-patch technique has been employed first. This technique requires division of the bridging leaflets, thus, among other issues, long-term function of the atrioventricular valves is of particular concern.Methods Between 1978 and 2001, 100 consecutive patients with isolated CAVSD underwent single-patch repair in our institution. Hospital mortality was 11%. Primary endpoints were clinical status, atrioventricular valve function, and freedom from reoperation in long term. Follow-up was obtained contacting the patient and/or caregiver, and the referring cardiologist.Results Eighty-three patients were eligible for long-term follow-up (21.0 ± 8.7, mean ± standard deviation [21.5; 2.1–40.0, median; min–max] years after surgical repair). Actual long-term mortality was 3.4%. Quality of life (QoL; self- or caregiver-reported in patients with Down syndrome) was excellent or good in 81%, mild congestive heart failure was present in 16%, moderate in 3.6% as estimated by New York Heart Association classification. Echocardiography revealed normal systolic left ventricular function in all cases. Regurgitation of the right atrioventricular valve was mild in 48%, mild–moderate in 3.6%, and moderate in 1.2%. The left atrioventricular valve was mildly stenotic in 15% and mild to moderately stenotic in 2%; regurgitation was mild in 54%, mild to moderate in 13%, and moderate in 15% of patients. Freedom from left atrioventricular-valve-related reoperation was 95.3, 92.7, and 89.3% after 5, 10, and 30 years, respectively. Permanent pacemaker therapy, as an immediate result of CAVSD repair (n = 7) or as a result of late-onset sick sinus syndrome (n = 5), required up to six reoperations in single patients. Freedom from pacemaker-related reoperation was 91.4, 84.4, and 51.5% after 5, 10, and 30 years, respectively.Conclusion Up to 40 years after single-patch repair of CAVSD, clinical status and functional results are promising, particularly, in terms of atrioventricular valve function. Permanent pacemaker therapy results in a life-long need for surgical reinterventions.
Keywords: complete atrioventricular septal defects; surgical repair; long-term results